Intercropping System for Growth and Yield in Local Varieties of Madura - Mahrus Ali; Sri Purwanti; Sri Hidayati (Agricultural Science, 2019)
This study aims to determine the growth and yield of Madura corn and Peanut with the intercropping system Sari. This study uses an experimental method (true experiment), defined as the method used to look for the effect of certain treatments on others under controlled conditions. In this case the writer uses the control class as a comparison so this study can also be called a pure experiment. The results showed that the best on Growth Results and Yield with intercropping system was local corn while the peanuts were not so good. Because at the time of harvest corn is harvested earlier than peanuts.